THE OBJECTIVES FROM THE RIGHTFUL PARTY ON THE PROPERTY APPRAISAL BY THE APPRAISER FOR THE COMPENSATION IN LAND PROCUREMENT - Syamsuni; Mohammad Effendy; Erlina (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2018)
The important role of the appraisal frequently raises conflicts between the government as the land procurement committee for development for public interest with the society as the rightful party upon the said object of land procurement. Therefore, it is deemed necessary that there is deliberation based on the principle of consensus. The Act has given the opportunity to the party who feels disadvantaged to counter in a form of objection referred to the court, so he or she can petition for compensation in conformity with his or her right. The consensus shall be on the form of the compensation (especially in a form of money). In case there is a disagreement on the amount of the compensation, such change on the amount of the compensation shall be made according to Article 37 paragraph (1) of Act Number 2 of 2012, but by filing a complaint to the court because the appraiser is a professional and independent institution whose tasks should based on Indonesian Appraisal Standard (SPI) and may not be contradictory to Indonesian Appraisal Code of Conduct (KEPI).